The Green Economy Role on Micro Waqf Bank Customers as Farmers in Banten Province - Fauzi, Muhamad; Dahlan, Rahmat; Syamanhudi, Muhammad (IAIN Ponorogo, 2022)
Micro waqf banks are formed by utilizing sharia social funds for poor productive communities around Islamic boarding schools. Traditional farmers, small, medium, and micro-enterprises do not understand the green economy principles as Maqashid Syariah approaches harmonizing human welfare and preserving nature in their business as valuable productive. The problem is the lack of understanding of the green economy of micro waqf bank customers in their business. This study aims to analyze the green economy's role on micro waqf bank customers as Farmer in Banten Province. This study uses a qualitative method with a grounded theory approach, while a purposive sampling technique for managers and customers of micro waqf banks. Data collection uses interviews, literature studies, and documentation, while data analysis uses design thinking. The results show optimizing the green economy role, including welfare, justice, environment, efficiency, and governance for micro waqf bank customer farmers. They can be implemented with social evolution models, including empathy, exploration, elaboration, exposure, execution, and expansion on micro waqf bank through financing, coaching, and empowerment on business sustainability. The implication is an optimization of the green economy role to understanding the concept and practice of micro waqf bank customers with a design thinking approach